ORISINALITAS HADIS ULAMA SUFI MELALUI METODE KASYF PERSPEKTIF IMAM AL-SUYUTI - Billah, Rodina; Muhid (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
Hadith criticism (Naqd al-Hadis) in the view of Hadith scholars has the highest urgency to determine the quality and originality of the Hadith of the Prophet Muhammad SAW. In Naqd al-Hadis itself, sanad criticism dominates over matan. As time progressed, the study of Hadith also developed which then gave birth to new methods in an effort to determine the originality of Hadith in accordance with the scientific tendencies pursued. One of these new methods is Kashf. Kashf as a method used in determining the originality of Hadith is proposed and approved by the majority of Sufi scholars. Whereas in the view of almost the majority of Hadith scholars, the Kashf method is considered to violate the scientific rules that they have created in an effort to preserve Hadith. al-Suyuti, as part of Hadith scholars, has a different view from the majority of other Hadith scholars. According to him, the Kashf method as an assessment of Hadith originality can be used as a second alternative. This is because al-Suyuti experienced Kashf himself, he often met with the Prophet Muhammad to ask about the authenticity of a Hadith. This research uses a literature review by analyzing documents that explain al-Suyuti's views on Kashf. Data processing is done by descriptive analysis method to find out Kashf in al-Suyuti's view. The results of this study show that al-Suyuti accepted the Kashf method as a second alternative in assessing the originality of Hadith. Al-Suyuti's acceptance requires that the Hadiths judged original through the Kashf method are in accordance with and do not violate the Hadiths that have been agreed upon by Hadith scholars. Keywords:  Kashf, Hadith, Originality, Al-Suyuti.